PEMANFAATAN SARI APEL SEBAGAI BAHAN BAKU PRODUK MAKANAN DAN MINUMAN DI KOTA BATU MALANG - Putri Asti Sidik; Lely Elviana; Anil Zikri; Endang Ayu Rahmawati; Suasa Suasa; Dandan Haryono; Nurhayati Hamid (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This study aims to analyze the utilization of apple extract as a raw material for food and beverage products in Batu City, Malang, using a qualitative approach. Batu City has strong potential for developing apple-based extract products, supported by the availability of high-quality apples, the tourism sector, and the distinctive added value of apple extract. However, MSME actors face several challenges, such as simple production technology, inconsistent quality and sanitation standards, limited packaging, and suboptimal digital marketing. Dependence on tourism and fluctuations in apple prices also pose threats to business sustainability. Opportunities for developing apple-extract products are considerable, including diversification into fermented beverages, jams, sauces, and dessert-based products, supported by government initiatives through training and production capacity improvement. SWOT analysis shows that effective development strategies include leveraging internal strengths and external opportunities, addressing weaknesses through innovation and training, and mitigating threats through strategic planning. Overall, apple extract is a valuable local resource that can support MSME economic growth and strengthen Batu City’s identity as an apple-based agro-tourism city, with successful development relying on innovation, improved production standards, packaging, and appropriate marketing strategies.